Sejarah dan Perkembangan Pondok Pesantren Kebon Jambu Al Islami Di Desa Babakan, Kecamatan Ciwaringin, Kabupaten Cirebon (1993-2006) - Edi Apriadi (UIN Sunan Gunung Djati Bandung, 2022)
Islamic boarding schools are the first Islamic education institutions to grow and develop in Indonesia. Many services are provided by the Islamic Boarding Schools for the:development of national education, one of which is in the form of contributions in shaping the young generation of intellectuals and integrity to continue the nation's struggle. Departing from this thought, the writer is interested in researching how. Therefore, he is interested in researching and writing about the History and Development of the Kebon Jambu Al Islami Islamic Boarding School in Babakan Village, Ciwaringin District, Cirebon Regency, because the Pesantren is one of-the Islamic boarding schools that can survive and develop. this modern age. This research methodology uses historical methods. The steps taken are heuristic, criticism, interpretation and historiography. Pondok Pesantren Kebon Jambu Al Islami is located in Babakan Village, Ciwaringin District, Cirebon Regency. Thisppesantrenswas founded by KH. Muhammad in 1993 M.Â